Bioprinting: 3D Printed Organ Models with Physical Properties of Tissue and Integrated Sensors (Adv. Mater. Technol. 3/2018). Issue 3 (13th March 2018) - Qiu, Kaiyan; Zhao, Zichen; Haghiashtiani, Ghazaleh; Guo, Shuang‐Zhuang; He, Mingyu; Su, Ruitao; Zhu, Zhijie; Bhuiyan, Didarul B.; Murugan, Paari; Meng, Fanben; Park, Sung Hyun; Chu, Chih‐Chang; et al.
Abstract : In article number 1700235, Robert M. Sweet, Michael C. McAlpine, and co‐workers designed and developed 3D printed organ models with physical properties of tissue and integrated sensors for surgical planning and rehearsal. The cover image illustrates an endoscope inserted in the channel of the prostate model with electrical signals in the background, depicting the concept of quantitative feedback from applying surgical tools on the model.